Landscapes without board. Routes of signs and drawings in the ionic territory in Calabria - Manuela Bassetta (Disegnare con, 2014)
The guidelines for the understanding and appreciation of the Park of Aspromonte in Calabria have implemented a route signs in Calabria to promote the image of city centers, they have created a system of communication to this territory. This process has converged drawing and description of the place in an experience in which the perspective drawing and the new instruments to the character (GIS) transform in a decisive manner the viewer's gaze. They cast him in a landscape between cities, smaller towns and territorial morphology, they create a link between the observed reality and what is possible to build and producing a visual structure of a new ecosystem-relational space.